2014
DOI: 10.1530/eje-14-0106
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in sclerostin and clinical characteristics in type 1 diabetes mellitus

Abstract: Background: Sclerostin is an osteocyte-derived inhibitor of the Wnt/b-catenin signaling pathway, which acts as a negative regulator of bone formation. Published data on sclerostin levels in type 1 diabetes mellitus (T1DM) are few. Objective: To evaluate gender differences in sclerostin serum levels and the association among sclerostin, bone mass, bone metabolism, and the main clinical characteristics of subjects with T1DM. Design and methods: A total of 69 patients with T1DM (mean age, 33.7G8.1; 49% males) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
4
15
2
8
Order By: Relevance
“…Our finding of no association of sclerostin with PTH was consistent with the similar finding in healthy children and healthy adults . In adult T1DM studies, no significant correlation of sclerostin with PTH was found in two studies , while Gennari et al reported a negative correlation in controls and a positive trend in T1DM patients, which has been attributed to a secondary raise in PTH levels due to lower 25(OH)D levels. Although we have evidence that PTH suppresses SOST gene, thus lowering sclerostin levels and leading to a negative correlation , the association of PTH with sclerostin in health and disease remains to be clarified with further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of no association of sclerostin with PTH was consistent with the similar finding in healthy children and healthy adults . In adult T1DM studies, no significant correlation of sclerostin with PTH was found in two studies , while Gennari et al reported a negative correlation in controls and a positive trend in T1DM patients, which has been attributed to a secondary raise in PTH levels due to lower 25(OH)D levels. Although we have evidence that PTH suppresses SOST gene, thus lowering sclerostin levels and leading to a negative correlation , the association of PTH with sclerostin in health and disease remains to be clarified with further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Increased sclerostin levels have also been reported in some [70, 71] but not all [72] clinical studies of adults with longstanding T1D, but not in children [73], possibly indicative of an exaggerated age-related increase in sclerostin levels in T1D [70]. Interestingly, this is similar to studies in adult patients with T2D, and with prediabetes, which also demonstrate increased serum sclerostin levels [72] [74-77]; in T2D, specifically, sclerostin levels correlate positively with glycated hemoglobin levels and with measures of insulin resistance [74, 76, 77], but negatively with bone-specific alkaline phosphatase (BSAP) [74].…”
Section: Effects Of Type 1 Diabetes On Osteocytesmentioning
confidence: 90%
“…Metabolic alterations, like insulin resistance, can contribute to explain the rising of sclerostin. Patients with Type 1 diabetes do not have insulin resistance, and serum sclerostin does not differ from controls [12, 34]. …”
Section: Discussionmentioning
confidence: 99%